Comparison of Auction Systems and Procedures Between Indonesia and Japan: A Study of the Principles of Transparency and Legal Certainty - Maskanah, Ummi; Khoerunnisa, Alsa Mala; Suherman, Dafina Nurulita; Zulaeha, Tuti (Golden Ratio of Law and Social Policy Review, 2025)
This study discusses the comparison of auction systems and procedures between Indonesia and Japan, focusing on the application of the principles of transparency and legal certainty. This study stems from the need to understand the extent to which these two principles are implemented in legally regulated auction mechanisms, as well as how the differences in legal approaches between the two countries affect the fairness and effectiveness of the auction system. This study uses a comparative juridical method with a normative-empirical approach, in which data is obtained through literature studies, analysis of legislation, and review of auction practices in both countries. The results show that Indonesia excels in the application of the principle of transparency through the digitisation of the e-auction system managed by the Directorate General of State Assets (DJKN). This system enhances efficiency and public information disclosure, but does not yet fully guarantee legal certainty, as post-auction disputes are still common and the legal protection for auction winners is weak. In contrast, Japan has an auction system based on the strong principle of the rule of law under the Civil Execution Act (Minji Shikkō Hō), with implementation under the supervision of judicial institutions that guarantee legal certainty and protection of buyers' rights. Transparency in Japan is realised in a measurable manner through procedural openness and judicial accountability. Analysis based on the theories of Good Governance and Rule of Law shows that Indonesia places more emphasis on the aspect of transparent management (governance), while Japan is more prominent in legal certainty (law). The two complement each other, because transparency without legal certainty has the potential to cause social uncertainty, while legal certainty without transparency can lead to closed bureaucracy. This study concludes that the ideal auction system is one that is able to integrate both principles in a balanced manner. Indonesia needs to strengthen the aspect of legal certainty, while Japan can adopt digitalisation to increase transparency.